Pelatihan Branding dan Strategi Promosi Digital untuk Meningkatkan Daya Saing Produk Lokal pada UMKM UMARA Kota Madiun - Juli Murwani; Nik Amah; M. Agus Sudrajat; Richo Diana Aviyanti (Universitas PGRI Madiun, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting regional economic growth. However, many MSMEs still face challenges in developing strong brand identities and implementing effective promotional strategies. Limited knowledge of branding and digital marketing has reduced the competitiveness of local products. This condition was also experienced by members of UMARA MSMEs in Madiun City, whose businesses include processed food, beverages, and handicrafts. Therefore, this community service program aimed to enhance participants’ knowledge and understanding of branding and digital promotion strategies to improve the competitiveness of local products. The program was implemented through several stages, including needs assessment, preparation, training, interactive discussions, and evaluation. The training involved 19 MSME participants from the UMARA community and was conducted through face-to-face learning sessions. The materials covered brand identity development, brand storytelling, packaging design, social media utilization, digital marketing strategies, and marketplace optimization. The results indicated that participants showed high enthusiasm throughout the training activities. They gained a better understanding of the importance of consistent branding, attractive product presentation, effective use of social media, and appropriate digital marketing strategies according to their business characteristics. Interactive discussions also increased participants’ awareness of product legality, halal certification, and the importance of maintaining brand consistency to strengthen consumer trust. Overall, this community service program contributed positively to improving the capacity of MSMEs in developing branding and digital promotion strategies. Continuous mentoring is recommended to ensure that the acquired knowledge can be effectively implemented, thereby enhancing the competitiveness and sustainability of local MSMEs.